Electrochemical plating of I125 on silver matrix for microsources - D. A. Podsoblyaev; N. A. Nerozin; V. V. Shapovalov; Yu. A. Yakovschits; A. S. Bolonkin; A. V. Dunin; A. A. Goverdovskiy (Biomedical Photonics, 2015)
A technique for plating of I125 on silver matrices by electrochemical plating at alkaline pH was developed and approved. The direct covering of I125 showed to be impossible and to take place only after pre-treatment of matrices by reagents with reductive and chelating properties. According to results of set of experiments the hydrazine hydrate was chosen as activating agent. The developed method includes preparatory activation of surface of silver matrices by processing with 0,01 mM hydrazine solution and then plating of I125 from NaI125 solution in 0,05 M alkaline solution with I125 volumetric activity of 50 mCi/ml (plating voltage of 950 mV). Radioactivity of samples made by developed method with time of coating for 30 or 60 min accounted for 1,12±0,12 mCi and 1.43±0.14 mCi, respectively. Thus, the developed method is efficient technique for plating of I125 on silver matrices, has replicable results and may be used for manufacturing of microsources.